2020
DOI: 10.1007/s12015-020-10000-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Mesenchymal Stromal/Stem Cells: Application in Critical Illness

Abstract: Critical illnesses including sepsis, acute respiratory distress syndromes, ischemic cardiovascular disorders and acute organ injuries are associated with high mortality, morbidity as well as significant health care system expenses. While these diverse conditions require different specific therapeutic approaches, mesenchymal stem/stromal cell (MSCs) are multipotent cells capable of self-renewal, tri-lineage differentiation with a broad range regenerative and immunomodulatory activities, making them attractive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 156 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…In this sense, the anti-inflammatory role of the MSC-derived EVs on T and B lymphocytes was observed regardless of the priming status of the MSCs used for their isolation. Whilst preclinical studies have demonstrated the therapeutic potential for MSC therapy in RA, optimization for their clinical use is an ongoing challenge and genetically engineered MSCs are being proposed to enhance their therapeutic potential [ 78 , 82 , 83 , 84 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In this sense, the anti-inflammatory role of the MSC-derived EVs on T and B lymphocytes was observed regardless of the priming status of the MSCs used for their isolation. Whilst preclinical studies have demonstrated the therapeutic potential for MSC therapy in RA, optimization for their clinical use is an ongoing challenge and genetically engineered MSCs are being proposed to enhance their therapeutic potential [ 78 , 82 , 83 , 84 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In viral vector delivery, insertional mutagenesis, immunogenicity, and limited carrying capacity are the main concerns. These concerns are minimal in nonviral delivery, which includes liposomes, plasmids, and miniplasmids; however, this approach has low transfection ability and transitory transgene expression ( 110 ). Due to MSC tropism in cancer tissues, several preclinical studies have investigated the possibility of using genetically engineered MSCs to target diverse types of cancer [ 111 113 ].…”
Section: Future Approaches To Enhancing Msc Potency For Covid-19 Treatmentmentioning
confidence: 99%
“…Genetic engineering methods to modify MSCs can be classified as those using viral transduction, nonviral transfection, or genome editing tools and techniques to overexpress therapeutic proteins that complement their innate properties (Figure 3) [43][44][45][46]. A growing body of evidence indicates that the paracrine, homing, immunomodulatory, anti-inflammatory, and tissue repair properties of MSCs can be strengthened through genetic modification [47]. As therapeutic agents and novel carriers, genetically modified MSCs target metastasis and efficiently provide a local high concentration of therapeutic agents that target a specific disease (Table 1).…”
Section: Therapeutic Potential Of Mscsmentioning
confidence: 99%